2013
DOI: 10.3758/s13420-013-0103-0
|View full text |Cite
|
Sign up to set email alerts
|

Natural category discrimination in chimpanzees (Pan troglodytes) at three levels of abstraction

Abstract: Two adult chimpanzees were presented with a series of natural category discrimination tasks on a touch screen computer, in which the discriminations varied in degree of abstraction. At the concrete level, discriminations could be made on the basis of single perceptual features, but at the more abstract level, categories were more inclusive, containing exemplars with variant perceptual features. For instance, at the most abstract level, the chimpanzees were required to select images of animals rather than nonan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 48 publications
3
16
0
Order By: Relevance
“…This is consistent with the prediction made for humans (Keil, 1988; Rosch et al, 1976), and possibly with findings from chimpanzees (Tanaka, 2001, although see Vonk et al, 2013), but not from squirrel monkeys, pigeons (Roberts & Mazmanian, 1988) or gorillas (Vonk & MacDonald, 2002). The gorilla subject in the present experiments seemed to learn the concrete level discrimination more rapidly despite the fact that she was simultaneously learning the DMTS task for the first time.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This is consistent with the prediction made for humans (Keil, 1988; Rosch et al, 1976), and possibly with findings from chimpanzees (Tanaka, 2001, although see Vonk et al, 2013), but not from squirrel monkeys, pigeons (Roberts & Mazmanian, 1988) or gorillas (Vonk & MacDonald, 2002). The gorilla subject in the present experiments seemed to learn the concrete level discrimination more rapidly despite the fact that she was simultaneously learning the DMTS task for the first time.…”
Section: Discussionsupporting
confidence: 91%
“…At the most abstract level, such as ‘animal’, superordinate category exemplars share even fewer perceptual features within a category but also share even fewer features with members of other abstract categories. The category ‘mammal’ may be considered superordinate to the basic level ‘dog’, but, in keeping with previously published studies (Roberts & Mazmanian, 1988; Vonk & MacDonald, 2002; Vonk & MacDonald, 2004; Vonk, Jett & Mosteller, 2012; Vonk et al, 2013), ‘mammals’ will be considered intermediate with ‘animal’ being considered the most abstract level category.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…In addition, the bears showed some degree of transfer to the control images depicting large and small foods (Vonk & Johnson-Ulrich, 2014). Thus, we have demonstrated rapid learning equivalent to that of great apes also tested in similar tasks (e.g., quantity discrimination, ambiguous cue paradigm, McGuire et al, 2017; natural category discrimination, Vonk, Jett, Mosteller, & Galvan, 2013;Vonk & Johnson-Ulrich, 2014;Vonk & MacDonald, 2002;2004), but we have not shown that bears can learn truly abstract constructs that are not tied to observable perceptual features, such as demonstrating relational learning or causal reasoning. Here, we present data from attempts to train bears to perform a matching-to-sample (MTS) task, and a serial list memory task.…”
supporting
confidence: 62%